Environmental sustainability in restaurants. A systematic review and future research agenda on restaurant adoption of green practices. Issue 4 (20th October 2022) - Madanaguli, Arun; Dhir, Amandeep; Kaur, Puneet; Srivastava, Shalini; Singh, Gurmeet
ABSTRACT: The adverse impact that restaurants have on the environment has received widespread attention in the last decade from both practice and academia. The current study aims to find, catalog, and synthesize the research body addressing green issues in the restaurant industry. We utilize the systematic literature review method to identify and analyze 68 research articles addressing environmental unsustainability problems in the restaurant industry. The research profile identifies the time trends of publication, key journals, countries studied, methods used, and restaurant types discussed in these studies. The results indicate that green restaurant research has grown exponentially recently and is now past its infancy. Through a detailed qualitative content analysis, we uncover five key thematic foci: stakeholders and their roles, sources of environmental unsustainability, green initiatives adopted by restaurants to address environmental unsustainability, outcomes of adopting green practices, and various ways of measuring greening practices. Research limitations and gaps of each of the themes are presented, with potential future research questions proposed for each gap. We then summarize the results of our review in a green restaurant ecosystem research framework.